Gestión del talento humano y su relación con productividad laboral en la empresa TRANSCASE SERVICIOS LOGISTICOS SAC - Trujillo, 2021 - Díaz Rojas, Claydi Melissa (2021)
The general objective of this research was to determine the relationship that exists between the management of human talent and labor productivity in the company TRANSCASE SERVICIOS LOGISTICOS SAC - Trujillo, 2021. The research is of an applied type, with a quantitative approach, it is descriptive and the sequence It is cross sectional and non-experimental design, the sample was made up of the 30 employees of the company. The results indicate that 26.67% of the employees indicated that the level of human talent management in the company Trancase Servicios Logísticos SAC is good, 43.33% indicated that it is regular and 30.00% indicated that it is bad. Therefore, we say that the level is regular. 33.33% of the employees indicated that the level of labor productivity in the company Trancase Servicios Logísticos SAC is good, 36.67% indicated that it is regular and 30.00% indicated that it is bad. The normality test was applied to the variables through the Shapiro-Wilk method and it was determined that the Rho-Spearman correlation coefficient was applied for the inferential analysis. It is concluded that there is a positive and significant relationship between the management of human talent and labor productivity in the company Transcase Servicios Logísticos SAC - Trujillo, 2021. That is, as long as you have good management of human talent, the productivity of the company will improve.